A Critical Study of Chador Hijab Metamorphism in TV Representation: a Semantic Study of" the Last Sin" and "Shout Silently" Series - Ali Jafari; Mohammad Mehdi Esmaeili (Taḥqīqāt-i Farhangī-i Īrān)
The changes of women veil in Iran after the Islamic Revolution and examining its cultural, social, political and economic aspects and outcomes is very important and has turned into a hot issue for cultural studies on veil in the Islamic Republic of Iran. "Chador' as an outstanding type of women veil in Iran has been affected b general trends of these changes and considerable parts of public culture and media atmosphere of Iran specially I RIB and cinema have represented these recent transformations. Although a great part of Iranian women actions on Chador take place in its traditional and classical form , considering these kinds of changes in the sign and function of Chador for some parts of social body and media representations of this veil makes this phenomenon very important and sensitive for cultural studies of dress and veil in Iran. This article has studied some degrees of semiotic, functional and semantic changes of chador hijab in I RIB series. Through 4 focus group interviews with 15 academic and seminarian women dressing traditional and classical Chador, this study analyzed the recent IRIB constructions of Chador dressing women and girls" which describes the wide functional and semantic transformations of Chador representation in IRIB dramatic programs. Thus some media and cultural malfunctions are observed in these progI'3rIlS and Chador hijab has degraded to an attractive and flashy "cape".